Conducir los asuntos de otras personas sin un poder en una pandemia: Ucrania y Polonia - Piotr Mysiak; Volodymyr Zubar; Dmytro Pestruiev (Ius Humani. Jornal do direito, 2020)
The Covid-19 coronavirus pandemic has caused changes in all areas of human life. The field of law is no exception to this list. In particular, the issues of conducting other people’s affairs without a power of attorney have become especially relevant, as social distancing and restrictions on social activity have led to a significant increase in the practical need for the application of this legal institution. The significance of this study is also important in connection with the comparative analysis of the normative aspect and the practical measurement of the application of the institute of conducting other people’s affairs without a power of attorney in Ukraine and Poland. These two countries are comparable in territory, number of citizens, legal tradition, but Poland has become member of the European Union, while Ukraine has remained on the sidelines of European civilization. The dialectical method, the method of comparative analysis and system analysis were chosen as the methodological basis of the research. The authors of the article concluded that institute of conducting other people’s affairs without a power of attorney is characterized by an increased level of social utility. In such cases, the one who protects the interests of others without a power of attorney, as a rule, acts not only in the interests of the individual but also in the interests of the society. Thus, it helps to protect single people, the elderly ones, disabled individuals and other groups which are socially unprotected and thus prevent the pandemic spread.